CORPORATE SOCIAL RESPONSIBILITY (CSR) ACTIVITIES AND BRAND EQUITY OF DIALOG AXIATA PLC, SRI LANKA. - Madubashini, D.K.; Pushpanathan, A. (Faculty of Business Studies, Vavuniya Campus of the University of Jaffna, 2020)
The concept of corporate social responsibility is an emerging concept and widespread notion among business communities and other aspects in recent decades. The Sri Lankan telecommunications industry has undergone several rounds of consolidation over the years. Mobile telecommunication covered a wide area of the population in Sri Lanka. Although, few types of research are conducted in Sri Lanka related to corporate social responsibility on brand equity especially in the mobile telecommunication industry. This study aims to analyze the effect of dimensions of CSR and Brand equity of Dialog Axiata PLC in Sri Lanka. Four dimensions – Economic responsibility, legal responsibility, ethical responsibility, and philanthropic responsibility – are considered independent variables of this study and Brand equity of the company is considered the dependent variable of this study. The data were collected from the 100 students of the Faculty of Business Studies, Vavuniya Campus and were entered into the SPSS – 20. Regression analysis used in this study for findings. The present study's findings indicated that the four dimensions of the CSR significantly affect the brand equity and positively correlated. Further, the result indicated that Ethical responsibility has positively associated with Brand equity than the other dimensions.
Keywords: Brand Equity.; Economic Responsibility.; Ethical Responsibility.; Legal Responsibility And Philanthropic Responsibility.